Genetic diversity of hepatitis viruses in West-African countries from 1996 to 2018 - Assih, Maléki (World J Hepatol, 2018)
The severity of hepatic pathology and the response to treatment depend on the hepatitis virus genotype in the infected host. The objective of this review was to determine the distribution of hepatitis virus genotypes in West African countries. A systematic review of the literature in PubMed, Google Scholar and Science Direct was performed to identify 52 relevant articles reporting hepatitis A, B, C, D, E and G viruses genotypes. Hepatitis B virus (HBV) genotype E with a prevalence of 90.6% (95%CI: 0.891-0.920) found in this review, is characterized by low genetic diversity. Hepatitis C virus (HCV) genotypes 1 and 2 represented 96.4% of HCV infections in West African countries, while hepatitis delta virus, hepatitis A virus, hepatitis G virus genotypes 1 and HEV genotype 3 were reported in some studies in Ghana and Nigeria. HBV genotype E is characterized by high prevalence, low genetic diversity and wide geographical distribution. Further studies on the clinical implications of HBV genotype E and HCV genotypes 1 and 2 are needed for the development of an effective treatment against this viral hepatitis in West African countries. Surveillance of the distribution of different genotypes is also needed to reduce recombination rates and prevent the emergence of more virulent viral strains.